Problematika Kekayaan Sumber Daya Alam Kalimantan dalam Puisi Di Sini Karya Dahri Dahlan (Kajian Semantik-Semiotik) - Dwi Rijaya Hakiki; Helvika Desmilianti; Widyatmike Gede Mulawarman (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research focuses on the problematics of Kalimantan's natural resource wealth in the poem "Di Sini" by Dahri Dahlan. The research used semantic theory and Roland Barthes's semiotics as the basis of analysis. The purpose of this research is to analyze the meaning contained in the language of the poem. In-depth interpretation is carried out by analyzing the language of poetry through denotation meaning, connotation meaning, and the relationship of cultural elements. This research is a literature study with a qualitative descriptive approach. The object of research is the poem "Here" contained in the poetry collection " Hal-Hal yang Pergi" by Dahri Dahlan. The data were obtained using listening and note-taking techniques. The results of the study outline two important meanings, (1) Dahri's poem "Di Sini" can be interpreted as a representation of loss and helplessness; and (2) Dahri Dahlan's poem "Di Sini" shows the wealth of natural resources as a form of real damage and loss.